IPR BOOKS Platform support balti academic community trough distance activities (Confluenţe Bibliologice, 2020)
The IPR BOOKS electronic system is one of the largest full-text resources in the educational and scientiﬁc literature. The pandemic has had far-reaching implications for USARB Scientiﬁc Library adjusted to lockdowns. There is no doubt librarians accelerated the distance work.In connection with this, the platform had oﬀered for academic commnunity free access to full texts and oﬀering free home access for students and teachers to full texts
Keywords: digital library; distance learning; digital content